The complete chloroplast genome of Atractylodes japonica Koidz. ex Kitam. and its phylogenetic inference - Mengmeng Shi; Hongbo Xie; Chunying Zhao; Linchun Shi; Jinxin Liu; Zhongsi Li (Mitochondrial DNA. Part B. Resources, 2021)
Atractylodes japonica Koidz. ex Kitam. is a perennial herbal plant, and its dried rhizomes have been widely used as traditional medicine in China and Japan. In this study, we assembled and annotated the complete chloroplast (cp) genome sequence of A. japonica using the high-throughput sequencing approach. The cp genome of A. japonica is 153,208 bp in length with the overall GC content of 37.7%, including two inverted repeat (IR) regions of 25,147 bp, which was separated by a large single-copy (LSC) region of 84,255 bp and a small single-copy (SSC) region of 18,659 bp. 113 unique genes were annotated in the genome, including 80 protein-coding genes, 29 represented tRNA genes, and four denoted rRNA genes. A maximum-likelihood phylogenetic analysis with 38 complete cp sequences showed that Atractylodes formed a monophyletic clade, and A. japonica and A. koreana formed a subclade in Atractylodes. This study provides the chloroplast genome structure features and phylogenetic relationship of A. japonica.